Multi-Stage Audit to Improve Accuracy of MDT Meeting Documentation on a General Adult Ward - Charles Pope; Raghu Vutla; Pankajam Nagarajan; Sophia Kim; Isabella Tea (BJPsych Open, 2025)
Aims: Stanley Ward is a 30-bed acute male ward in Wakefield. Quality of MDT meeting documentation was poor. We audited documentation quality in three cycles from March to November 2024, with interventions.